Behavior determinants of malaria incidence in endemic areas of Kaligesing District, Purworejo Regency - Fitriani, Dwi; Raharjo, Mursid (BKM Public Health and Community Medicine, 2025)
Purpose: The purpose of this study is to analyze the behavior of the community with the incidence of malaria in Kaligesing District. Methods: Using quantitative methods that were analyzed observationally with case-control studies. Sampling employed purposive sampling techniques, involving a total of 80 respondents, comprising 40 case group respondents and 40 control group respondents each. The instrument used is a questionnaire. Results: The results showed that the case group had lower knowledge (52.5%), which was higher compared to the control group (30%), as determined by the chi-square test with a p-value of 0.069. Negative attitudes were more prevalent in the case group (52.5%) compared to the control group (40%), as indicated by a chi-square test with a p-value of 0.370. Low action was found in the case group (50%) compared to the control (17.5%) and based on the chi-square test obtained a value of p=0.005, OR=4.714 and 95% CI OR (1.693 – 13.131) meaning that people who have less action on malaria prevention and control are 4.714 times more at risk of developing malaria than with people who have good measures on malaria prevention and control. Conclusion: There is no relationship between knowledge and attitudes with the incidence of malaria, and there is a relationship between actions and the incidence of malaria.